P790 Epidemiology, clinical characteristics, evolution and treatments in newly diagnosed inflammatory bowel disease (IBD): results from the nationwide EpidemIBD study of GETECCU. (25th January 2019) - Chaparro, M; Barreiro-de Acosta, M; Benítez, J; Cabriada, J; Casanova, M; Ceballos, D; Esteve, M; Fernández, H; Ginard, D; Gomollón, F; Lorente, R; Nos, P; et al.
Abstract: Background: Updated data on the incidence, evolution and treatment strategies used in IBD management in South Europe is needed. This is the largest study on the recent epidemiology of IBD in Spain. The aims of this study were (i) to assess the incidence of IBD in Spain; (ii) to describe the main epidemiological and clinical characteristics of patients at diagnosis and the evolution of the disease; and (iii) to explore the use of treatments in the biological era. Methods: Prospective and population-based nationwide registry. Adult patients diagnosed with IBD Crohn's disease (CD), ulcerative colitis (UC) or IBD unclassified (IBD-U)- during 2017 in the 17 Spanish regions were included and will be followed-up for 5 years after diagnosis. Treatment was grouped into 5 categories: mesalazine (oral or topical), steroids (intravenous, oral or topical), immunomodulators (thiopurines, methotrexate or cyclosporine), biologics (anti-TNF, vedolizumab or ustekinumab) and surgery. Cumulative incidence of exposure to each of the studied treatments was estimated by Kaplan–Meier curves. Results: In total, 3627 incident cases of IBD diagnosed during 2017 from 111 centres covering over 23 millions of adult inhabitants (about 50% of the Spanish population) comprise the study cohort. The overall incidence (per 100000 person-years) of IBD was 14.3: 6.5 for CD, 7.1 for UC, and 0.7 for IBD-U (Figure 1). During a median follow-up of 10 months, 33 (2.4%) CD patients progressed to a more severe phenotype, and 2 (0.01%) UC patients to more extensive involvement. The cumulative incidences of the different treatments are shown in Figure 2. Conclusions: The incidence of IBD in Spain is relatively high and similar to figures reported in Northern Europe. IBD patients require the use of substantial diagnostic and therapeutic resources, which are higher in CD than in CU. One third of patients are hospitalised in the first year after diagnosis and over 5% undergo surgery. Our results highlight the high burden of IBD as well as the important challenges faced by healthcare systems to manage this costly and complex disease.